Multisession, dual-task psychological refractory period practice benefits older and younger adults equally. - Allen PA; Ruthruff E; Elicker JD; Lien M (Experimental Aging Research)
The authors tested 18 younger adults and 18 older adults on four sessions in a psychological refractory period (PRP) paradigm, to see whether older adults can benefit as much from dual-task practice as younger adults. Task 1 involved tone discrimination and Task 2 involved simultaneous letter-matching. The stimulus onset asynchrony (SOA) between the tasks was either 50, 150, 300, or 900 ms. Although older adults showed a larger PRP effect than younger adults, there were no group differences in the practice=training benefit. These results differ from Maquestiaux, Hartley, and Bertsch (2004, Psychology and Aging, 19, 64 --667, Experiment 1), who found that age differences in PRP effects became progressively larger with increased practice. These findings, along with the simultaneous-presentation, dual-task work of Kramer, Larish, and Strayer (1995, Journal of Experimental Psychology: Applied, 1, 50--76) and Bherer et al. (2005, Psychology and Aging, 20, 695--709; 2006, Acta Psychologica, 123, 261--278), suggest that older adults can benefit as much as younger adults from dual-task training.